The Effect of K3 Implementation on Productivity using SEM -PLS - Wulandari, Reza (Universitas Putra Indonesia YPTK Padang, 2025)
Occupational safety and health is an effort to create a workplace that is comfortable, safe, healthy and free from environmental pollution, so that workers are protected from accidents at work, so that in the end they are able to increase efficiency in any aspect and are also able to increase productivity. The conflict that occurred in the CNG Tofu Factory was the lack of implementation based on K3 as a result of which work accidents were not uncommon and decreased productivity. The purpose of this study was to determine the impact of the application of K3 on productivity at the CNG Tofu Factory. The method used in this research is the Structural Equation Modeling - Partial Least Square (SEM-PLS) method. The data used is the output based on the distribution of questionnaires to 22 respondents which is then processed using the SmartPLS application. The results obtained indicate that the work safety variable (X1) has a positive and significant effect on the productivity variable (Y) = 53.3%. And the occupational health variable (X2) has a positive and significant effect on the productivity variable (Y) = 44.6%. Thus, it can be concluded that the application of K3 has a positive and significant effect on productivity (Y) = 86.2%.